Pediatric tracheal dimensions on computed tomography and its correlation with tracheostomy tube sizes. (22nd June 2019) - Naina, P.; Syed, Kamran Asif; Irodi, Aparna; John, Mary; Varghese, Ajoy Mathew
Abstract : Objective: Age‐based formulas for selecting the appropriate size of tracheostomy tubes in children are based on data on tracheal dimensions. This study aims to measure the tracheal dimensions of Indian children by computerized tomography (CT) and to compare this with the dimensions of age‐appropriate tracheostomy tubes. Methods: CT scans of children aged less than 16 years that were taken for indications other than respiratory distress were included. Tracheal diameters at the tracheostomy point and tracheal length from the tracheostomy point to the carina were calculated from the scans. These dimensions were correlated with age, weight, and height. The measurement on the CT scan was used to predict the appropriate size of tracheostomy tube, which was compared with the tracheostomy tube sizes. Results: Two hundred and fourteen CT scans of children aged below 16 years were included in the study. On multiple logistic regression analysis, tracheal diameter correlated well with age and weight ( P = 0.04 and 0.001, respectively), whereas tracheal length correlated well with age and height of the child ( P = 0.03 and 0 < 0.001, respectively). On comparison with dimensions of the tracheostomy tube, tracheal diameter correlated well, and the length was found to be longer than needed to prevent endobronchial intubation. The regression value was used to predict the size of an ideal tracheostomy tube. Conclusion: Tracheal diameter of Indian children correlates well with the outer diameter of age‐appropriate tracheostomy tubes, but the length of these tubes is longer than the ideal length. This would necessitate a change in the design of these tubes. Level of Evidence: 2b Laryngoscope, 130:1316–1321, 2020